INFLUENCE OF CUSTOMS AND TARIFF REGULATION MEASURES ON IMPORT SUBSTITUTION OF MEAT AND FOOD BY-PRODUCTS OF POULTRY ON THE RUSSIAN MARKET - D. E. Barsegyan (Вестник университета)
In order to protect the national interests of the Russian Federation, from 2014 to the present, the import  substitution policy has been applied, which is a priority in economic policy. The article considers the dynamics of exports and imports of meat and food by-products of poultry on the Russian market. The paper analyses the influence of customs and tariff regulation measures on the dynamics of exports and imports of meat and food by-products of poultry on the Russian market as an object of the import substitution program. The author selected the following measures as the analysed measures: tariff quotas for the import of meat and food by-products of poultry on the Russian market, as well as import and export customs duties on the studied category of goods.